Tanggung Jawab Hukum Perdata Travel Smarthajj Atas Kegagalan Pemberangkatan Jamaah Umroh - La Ode Muhammad Saleh Saputra; Ayib Rosidin; Asri Sarif; Tia Yuliana (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2025)
The increasing interest of Indonesians in performing the Umrah pilgrimage each year has fueled the rapid growth of Umrah travel agencies. However, this growth has also given rise to various legal issues, such as default by travel agencies that fail to fulfill their agreements regarding the departure of pilgrims. The purpose of this study is to analyze the forms of default by Umrah travel agencies, the legal responsibility of travel organizers, and the forms of legal protection for injured pilgrims. The research method used is normative legal research with a statutory and conceptual approach, as well as case studies of several decisions related to Umrah disputes. The results indicate that Umrah travel agencies that fail to depart pilgrims have committed a default as stipulated in the Civil Code and are therefore obligated to provide a full refund, compensation, and fulfillment of consumer rights. Furthermore, it was found that weak supervision, minimal legal literacy of pilgrims, and non-compliance of travel agency practices with Ministry of Religious Affairs regulations are the main factors contributing to the disputes. This study concludes that strengthening regulations, increasing government oversight, and providing legal education for pilgrims are crucial steps to ensure legal certainty and consumer protection in organizing Umrah travel in Indonesia.